Size differences among immunoglobulin heavy chains from phosphorylcholine-binding proteins. - Rudikoff, S (1976)
The entire sequences of the heavy chain variable regions of M167 and TEPC 15 (phosphorylcholine-binding myeloma proteins of BALB/c origin) have been determined. These sequences are compared with the phosphorylcholine-binding protein M603. T15 differs from M603 at four positions, all of which are located in antigen-binding complementarity regions. M167, in addition to having differences in the complementarity regions, also has five substitutions in the conserved framework portion of the variable region when compared to T15 and M603. Each of the three proteins has a different length in the third complementarity region. It is unlikely that complementarity regions of different lengths associated with similar framework regions could be generated by proposed mechanisms of somatic mutation which are generally limited to point mutations. It appears more likely that these products are directly encoded by different structural germ line genes.